Penilaian Risiko K3 Pada Praktikum Farmakognosi Di Laboratorium Program Studi Farmasi Terkait Dengan Risiko Covid-19 - Faizal Riza Soeharto; Priska Ernestina Tenda; Maria Imakulata Masiya Indrawati (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
Safe and healthy working conditions the basic for decent work where working conditions like this are even more important today, given the importance of ensuring K3 in managing the Covid-19 pandemic and the ability to return to work. This study aims to determine the risks of making phyto-vegetable simplicia in the Pharmacognosy practicum which related to the risk of Covid-19 and research is descriptive observational. Population i.e work at Pharmacognosy practicum and the sample is job on the manufacture of phyto-vegetable simplicia taken purposively. The research instrument, the researcher identifies the potential hazards (loss) of making simplicia and determines the level of risk. The technique of collecting data i.e. observing step of making simplicia with K3 hazard identification form. The analysis technique i.e. observational data of making simplicia and then determined the potential hazards, cause, the impact, calculated the risk value and level of risk. The results show of making simplicia has potential loss in the form of be inhalated, repetitive movements, and mishandling that can affects the final result with the dominant consequence of discomfort. Dominant risk value 20 (extreme) at the collecting raw materials and wet sorting. As a whole show a low risk meaning acceptable so practicum can do but supervision is needed while low risk of spreading Covid-19 achieved with reducing number exposed chance, minimize contact with the source of transmission i.e. protocols health optimal that so impact disease incidence is also low.